Clinical and molecular characterization of a patient with MBTPS1 related spondyloepiphyseal dysplasia: Evidence of pathogenicity for a synonymous variant - Yuan, Yeqing; Zhou, Qiaoli; Wang, Chunli; Zhou, Wei; Gu, Wei; Zheng, Bixia (Frontiers in Pediatrics, 2023)
Background A novel autosomal recessive skeletal dysplasia resulting from pathogenic variants in membrane-bound transcription factor peptidase, site 1 (MBTPS1) has been recently delineated. To date, only three patients have been reported. Methods In this study, we reported the clinical and molecular features of a Chinese boy who was diagnosed with spondyloepiphyseal dysplasia. The effects of variants on mRNA splicing were analyzed through transcript analysis in vivo and minigene splice assay in vitro. Results The proband mainly showed short stature, special facial features, cataract, hernias, and serious sleep apnea syndrome. Growth hormone stimulation tests suggested the boy had growth hormone deficiency. Imaging examinations suggested abnormal thoracolumbar vertebrae and severely decreased bone mineral density. Genetic analysis of MBTPS1 gene revealed two novel heterozygous variants, a nonsense mutation c.2656C > T (p.Q886*, 167) in exon 20 and a synonymous variant c.774C > T (p.A258=) in exon 6. The transcript analysis in vivo exhibited that the synonymous variant c.774C > T caused exon 6 skipping. The minigene splice assay in vitro confirmed the alteration of MBTPS1 mRNA splicing and the exon skipping was partially restored by an antisense oligonucleotide (ASO) treatment. Conclusion Notably, we report a Chinese rare case of spondyloepiphyseal dysplasia and validate its pathogenic synonymous variant in the MBTPS1 gene.